Intelligent, model-based control towards the intensification of downstream processes. (4th October 2017) - Papathanasiou, Maria M.; Steinebach, Fabian; Morbidelli, Massimo; Mantalaris, Athanasios; Pistikopoulos, Efstratios N.
Highlights: Development of advanced multi-parametric controllers for a semi-continuous periodic separation process. Novel control strategy tracking the integral of the outlet component concentration leading to tighter process monitoring. Measured disturbances arising from variations in the feed stream thus enabling process integration are considered. Abstract: Process Intensification (PI) has been gaining increasing interest as industrial trends urge a shift towards more eco-efficient processes of significantly decreased operation and capital costs. In this direction we focus on the development of advanced control strategies of the Multicolumn Countercurrent Solvent Gradient Purification Process (MCSGP), an industrial, semi-continuous, chromatographic process, used for the purification of several biomolecules. We present a novel control approach that manages to drive the process towards continuous, sustainable operation. The presented controllers are designed within the PARametric Optimization and Control (PAROC) framework/software platform that enables the development of intelligent, model-based controllers through a step-by-step approach. The controllers are successfully tested against various disturbance profiles and they manage to track the predefined setpoints without significant offset.